Adipose-Derived Stem Cells Improve the Aging Skin of Nude Mice by Promoting Angiogenesis and Reducing Local Tissue Water. (11th January 2021) - Qin, Feng; Zhang, Wenchao; Zhang, Mingzi; Long, Xiao; Si, Loubin; Li, Zhenjiang; Huang, Jiuzuo; Wang, Xiaojun
Abstract: Background: Adipose-derived stem cells (ASCs) are considered promising cells for skin rejuvenation. However, whether the angiogenetic effect of ASCs plays an important role in the treatment of aging skin and its influence on skin tissue remain elusive. Objectives: The aim of this study was to evaluate the effect of ASCs on angiogenesis and local tissue water (LTW) in the aging skin of nude mice. Methods: Twelve nude mice were randomly divided into a UVB-induced photoaging group and a natural aging group. After the mouse model had been established, ASCs and phosphate-buffered saline (PBS) were then each injected into different sides of the dorsal skin of the mice. Blood perfusion and LTW content were measured. After 7 weeks, mice were killed, and skin samples were collected to measure the thickness of the dermis, the density of the capillaries, and the expression of angiogenic growth factors. Results: ASC therapy significantly increased the thickness of the dermis, the number of capillaries, and the expression of some angiogenic growth factors (vascular endothelial growth factor, insulin-like growth factor 1, and epidermal growth factor). At 7 weeks after injection, blood perfusion was significantly higher on the side injected with ASCs than on the side injected with PBS. LTW content was increased in the PBS-injected side, but the ASC-injected side showed no significant changes over time. Conclusions: ASCs increased dermal thickness, promoted angiogenesis, and reduced LTW content in the skin of photoaging mice, providing a potential clinical therapy for skin rejuvenation.